The impact of utilizing an electronic dummy device on the development of motor response speed and the acquisition of the straight punch technique in boxing for novice practitioners - Aqeel Abdul Jabbar Abdul Rasool (Eximia, 2025)
The present study aims to identify the impact of utilizing an electronic doll in the development of motor response speed. In addition, novice pugilists are instructed in the proper techniques for executing right and left straight punches. The researcher employed the experimental method to design the experimental single group to align with the research sample and problem. The sample comprised six novice players from the Al-Mahawal Boxing Sports Club. The subjects of this study are members of the experimental research group who are between the ages of 12 and 13. An exploratory experiment was conducted on two novices outside the research sample. This is to ensure the suitability of the exercises, according to the work of the device and the tests used. Concurrently, the pre-tests were conducted, and the modules were implemented using the electronic dummy device. The total number of educational units completed was 18, with three units being completed per week for a period of six weeks. Following the conduction of the dimensional tests, the results were obtained and statistically processed using the SPSS statistical bag. The researcher’s findings indicated that the electronic dummy device is an effective educational tool for enhancing the speed of motor response and facilitating the acquisition of boxing skills among novice practitioners. It has been demonstrated to facilitate the enhancement of fundamental competencies. The researcher’s most significant recommendations included the necessity of incorporating devices and tools into educational or training units. This is attributable to its role and effectiveness in the development of performance.